Multidrug strategies are effective in the treatment of severe experimental pancreatitis - Werner, Jens; Hartwig, Werner; Hackert, Thilo; Kaiser, Heiko Andreas; Schmidt, Jan; Gebhard, Martha-Maria; Büchler, Markus W.; Klar, Ernst (Surgery, 2012)
Background: Trypsinogen activation, oxygen radicals, cytokines, leukocyte infiltration, and pancreatic ischemia are important steps in the pathogenesis of necrotizing pancreatitis and associated systemic complications. Several drugs that inhibit those pathogenetic steps attenuated biochemical and histologic changes, while survival remained low. The aim of the present study was to evaluate the benefit of multidrug approaches compared to monotherapies on organ injury and survival in acute experimental pancreatitis in the rat model of retrograde bile injection combined with intravenous cerulein. Methods: Necrotizing pancreatitis was induced in rats. After a therapy-free interval of 6 hours, 10 treatment regimens were evaluated: multidrug regimen 1, which contained the protease inhibitor gabexate mesilate, oxygen-free radical scavengers, nitric oxide donor L-arginine, a platelet-activating factor antagonist, and antibodies against intracellular adhesion molecule-1 (ICAM-1) dissolved in dextran, was compared to multidrug regimen 2 (dextran, acetylcysteine, L-arginine, and anti-ICAM-1), monotherapies of each of the drugs, and standard intravascular volume replacement. Results: Both multidrug regimens significantly reduced pancreatic and systemic injury and microcirculatory disturbances compared to any of the monotherapies. Treatment with regimen 1 decreased 24-hour mortality to 0% and increased long-term survival to 85% (standard therapy, 70% and 15%, respectively). Multidrug regimen 2 was as effective as regimen 1. Conclusion: Treatment of acute necrotizing pancreatitis with multidrug regimens significantly decreases short-term mortality compared to monotherapies. Moreover, multidrug strategies are still effective after a wide therapeutic window. Key to this effective therapy is the inhibition of microcirculatory disturbances and of the systemic inflammatory response. The experimental superiority of the multidrug approach should be confirmed in a clinical trial.